FACTORS DRIVING GEN Z PURCHASING DECISIONS TOWARDS STREET FOOD WITH THE MEDIATING ROLE OF PURCHASE INTENTION - Riska Widya Abiba; Muhtadi Ridwan; Khusnudin (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: This study examines the influence of product knowledge, halal awareness, subjective norms, and attitudes on street food purchasing decisions through purchase intention as a mediating variable. Method: This research includes quantitative research with an explanatory research approach. The population used in this study is Gen Z Muslims in Surabaya. The sample in this study amounted to 330 respondents obtained from the sampling technique, namely accidental sampling. To test the hypotheses built using partial least square (PLS) analysis techniques with Smart-PLS Version 3.2.9 software tools. Results: The results stated that product knowledge, halal awareness, attitude, and subjective norm are not significant effect on purchasing decisions partially. However, all dependent variables affect decisions through purchase intention. Means, customer intentions become critical point before their making purchases. Conclusion and suggestion: In summary, understanding purchase intention through customer behavior is essential to be considered by business actors to increase consumer assessment of these products. In this case, business actors need to educate related to food regulation such as having halal logo and ensure the product safety. By having proper assessment food vendors will be able to promote their product and increase customer purchasing intention. Furthermore, policymakers and related stakeholders also need to support food regulation and safety by having proper law and supply chain of halal ingredients.